The Role of Indigenous Knowledge Systems in Cultural Heritage Preservation under NEP 2020 - Atul Khajuria; Stephen Monday; Christian Gendemeh; J. Samuel Kamanda; Eric Kwasi Ellison (International Journal of Trends in Humanities, 2025)
In Introduction, This study explores the roles of India’s National Education Policy (NEP) 2020 in cultural heritage preservation through indigenous knowledge systems. These include traditional arts, crafts, ecological practices, and languages. It also includes perspectives through gender and regional lenses on this integration. In Methodology, Confirming the study, a survey was held with 2,300 participants, with an equal split of male, female and non-binary, from rural and urban settings. The survey covered areas of knowledge, implementation, impact, and challenges of indigenous knowledge in education. SPSS was put to use for data analysis using descriptive (mean, standard deviation) and inferential (t-tests, ANOVA) statistics. A significance level of α=0.05 was applied. In Results, Respondents agreed that indigenous knowledge should have a role in education (average score: 4.2/5). Women (4.4) provided more support than men (4.0), and respondents from rural areas showed greater awareness and more support than those from urban areas. Participants identified teachers and resources as the major barriers77 (65%). There was a high degree of support (average score: 4.3) for the implementation of specialist teacher training programs to address these challenges. In Conclusion, These results reflect strong support for the inclusion of indigenous knowledge systems in education as called for in NEP 2020. But major hurdles remain, including the lack of trained teachers and scarce resources. Correcting the problems will require focused investments, training teachers and developing curricula. Educational institutions, local communities, and holders of indigenous knowledge will need to work together to ensure that cultural preservation is indeed — not just word — indeed something much.
Keywords: Indigenous Knowledge Systems; NEP 2020; SPSS analysis; community-based education; cultural continuity; cultural heritage preservation; curriculum development; educational integration; gender differences in education; gender inclusion; national education policy 2020; rural-urban differences; survey study; teacher training; traditional practices